PERAN DECOMPESER DALAM PEMBUATAN KOMPOS DARI LIMBAH PADI DAN LIMBAH SAWIT - Nurlianti Nurlianti; Prihanani Prihanani (University of Prof. Dr. Hazairin, SH, 2018)
The research aims to find a better and cheaper type of decomposer in the composting process with rice straw base and palm oil waste. The benefit of this research is for farmer groups to produce faster compost fertilizer with better compost quality by using effective and cheaper decomposer. The compost can be used to increase the income and can also improve the sanitation of the rice fields and oil palm plantations and most importantly reduce the costs of wet land paddy farming and cultivation of palm oil. The results showed that both waste materials can be used for bokhasi production by giving the three decomposer as treatment, but the use of EM-4 activator for the compost base material of palm-based compost is called bokhasi and the use of Tricho-G activator for the straw-based raw material compost known as Trichokompos shows physical quality as well as better chemical quality than other treatments. The use of activators from EM-4 cultures shows the quality of the compost produced is not too different from other decomposer so it can be used as an alternative to reduce the cost of compost production.